The effect of silica content to partial discharge characteristic of low-density polyethene and natural rubber blend as the electrical insulator - Aulia Aulia; Eka Putra Waldi; Darwison Darwison; Dwi Gustiono; Novizon Novizon; M. Heru Setiawan; M. A. Hafizi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
The dielectric properties of low-density polyethylene natural rubber (LDPE-NR) biopolymeric insulating materials can be improved by adding the silica nanoparticles in a certain percentage of weight (w%). In the present study, four types of bio-nano polymeric samples were prepared. To each sample, the nanosilica particles with wt% 1.5%, 3%, 4.5% and 6%. As one characteristic of dielectric, the partial discharge (PD) characteristics, each sample has been tested for 1 hour under AC high voltage field, and the pulses were counted for each sample and grouped into positive and negative pulses. The PD pattern was also plotted based on X-Y axes, namely Φ-q-n pattern. It was found that the number of positive and negative partial discharge (PD) pulses for each silica sample after 60 minutes of testing varied for all samples. It is also found that samples with a higher percentage of nanosilica had fewer PD pulses. The PD pattern in lower w% of silica was identified in the 90 degrees mostly in containing This indicates that w% of nanosilica particles can improve the PD resistance or the insulation quality of LDPE-NR insulation materials.